Stressful Life Events and Psychological Well-being in a Brazilian Sample of Older Persons: The Role of Resilience - Couto, Maria Clara Pinheiro de Paula (2015)
The authors thank Pedro Soares, Débora Verdi, Hanna Sainio and Ivalina Porto for their work on the data collection and the community centers where the data was collected: Centro de Esportes, Lazer e Recreação para o Idoso (CELARI/UFRGS), Meninos da Bocha – Parque Alim Pedro, Universidade do Adulto Maior (UAM/IPA), Núcleo de Atendimento à Terceira Idade (NATIEx/Policlínica Militar de Porto Alegre), Projeto QualiVida e Núcleo Universitário da Terceira Idade (NUTI/FURG).